Analisis Struktur Organisasi Universitas Telkom - Pangarso, Astadi; Nurrahmasari, Intan Garnita; Nurnida, Ida; Rengganis, Renni; Setiawati, Cut Irna (Institute fo Managing and Publishing Scientific Journals, 2016)
In the modern view, the structure becomes an important part in the analysis of the organization because structure as a part of an organization that is directly in contact with the environment. This study was conducted to analyze the organizational structure of Telkom University (Tel-U) at this time which means seeing how the Tel-U organizational structure of complexity, formalization, centralization, and coordination aspect based on the viewpoint of faculty.The variable used in this research that an organizational structure which consist of four dimensions (complexity, formalization, centralization, and coordination). The sample in this study is Management Coordinator Transformation and Affairs Chief in each faculty of Tel-U with purposive sampling. Processing data using descriptive analysis using Microsoft Excel as the analysis tool. The result showed that the organizational structure of Telkom University as a whole are included in the category sufficient good (respectable) with an average total score of 68%.